2005
DOI: 10.1111/j.1440-1711.2005.01342.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibody blockade of Thy‐1 (CD90) impairs mouse cytotoxic T lymphocyte induction by anti‐CD3 monoclonal antibody

Abstract: Summary Thy-1 (CD90) expressed by mouse T cells is known to have signal transducing properties, but the ability of Thy-1 to enhance cytotoxic T lymphocyte (CTL) development is not well understood. Here we show that stimulation of mouse T cells with monoclonal antibodies (mAb) to CD3, CD28 and Thy-1 (clone G7), which were coimmobilized on polystyrene microbeads, resulted in a greater proliferative response than stimulation with only anti-CD3 and anti-CD28 mAb, indicating that Thy-1 cross-linking enhanced T cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Inhibition of T cell activation through down-regulation of TCR-CD3 expression can be mediated by an anti-CD90 antibody [ [19] ] . Furthermore, Thy-1 signaling promotes the in vitro generation of CTLs that kill target cells in a granule-dependent fashion [ [20] ] . To examine whether or not this age-associated change of CD90 expression contributes to the decreased T cell response with aging, we compared the responses of CD90 hi and CD90 low CD8 T cells of aged Tg mice.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of T cell activation through down-regulation of TCR-CD3 expression can be mediated by an anti-CD90 antibody [ [19] ] . Furthermore, Thy-1 signaling promotes the in vitro generation of CTLs that kill target cells in a granule-dependent fashion [ [20] ] . To examine whether or not this age-associated change of CD90 expression contributes to the decreased T cell response with aging, we compared the responses of CD90 hi and CD90 low CD8 T cells of aged Tg mice.…”
Section: Resultsmentioning
confidence: 99%
“…CD90 is a glycosyl phosphatidylinositol-anchored membrane glycoprotein of the immunoglobulin superfamily expressed mainly on the surface of leukocytes. 65 This marker is involved in cell-cell and cell-adhesive matrix interactions. Yang et al found that the CD90-positive subpopulation showed a distinct higher tumorigenicity and metastatic potential in a mouse xenograft model when compared with CD90-negative counterparts.…”
Section: Cd90mentioning
confidence: 99%
“…In contrast, the majority of studies using anti-CD90 Abs demonstrated a mitogenic role for CD90 in T cell activation [22,25,31,33]. One anti-Thy-1 Ab, clone G7, augmented TCR/CD28-driven T cell proliferation [33]. Another anti-CD90 Ab, 30-H12, had no potential to activate T cells, but, was able to block CD90 signaling as a soluble form, resulting in inhibition of the anti-CD3-induced proliferation of CD4 T cells [33], suggesting an important co-stimulatory role for CD90 signaling in mouse T cell activation.…”
Section: Discussionmentioning
confidence: 79%
“…These reports suggest that CD90 functions as a negative regulator of TCR-mediated signaling. In contrast, the majority of studies using anti-CD90 Abs demonstrated a mitogenic role for CD90 in T cell activation [22,25,31,33]. One anti-Thy-1 Ab, clone G7, augmented TCR/CD28-driven T cell proliferation [33].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation